Certainty as a moderator of feedback reactions? A test of the strength of the self-verification motive - ANSEEL, Frederik (Institutional Knowledge at Singapore Management University, 2006)
The present study investigated whether employees are merely interested in hearing good news about themselves, as predicted by self-enhancement theory, or are more interested in feedback that confirms their self-concept, as predicted by self-verification theory. We examined in a field study whether self-view certainty serves as a moderator and strengthens the effect of congruence between individuals' self-views and the performance feedback they receive about these self-views on feedback reactions. Polynomial regression results revealed that people mainly reacted favourably to positive feedback. Prior self-views did not play a key role in explaining feedback reactions. As feedback scores were the main determinant of feedback reactions, it seems that feedback reactions are dominated by self-enhancement strivings and that self-verification strivings are less prominent. Little support was found for the moderating role of self-view certainty.